2023
DOI: 10.2147/jmdh.s419847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ChatGPT on Teleconsultants in Healthcare: Perceptions of Healthcare Experts in Saudi Arabia

Abstract: This study aims to investigate the impact of ChatGPT on teleconsultants in managing their operations and services. Methods: A qualitative approach with focus groups is adopted in this study. A total of 54 participants with varying degrees of experience using AI such as ChatGPT in healthcare, including 11 physicians, 24 nurses, eight dieticians, six pharmacists, and five physiotherapists providing teleconsultations participated in this study. Results: Twelve themes including informational support, diagnostic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…By leveraging the capabilities of ChatGPT, professionals can benefit from its insights and assistance, ultimately leading to improved outcomes for patients. By sharing insights and potential data on the AI platform, physicians may promote greater communication among other doctors and patients ( 54 ). This way, physicians can make better decisions by accessing the patients’ data and opinions from colleague doctors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By leveraging the capabilities of ChatGPT, professionals can benefit from its insights and assistance, ultimately leading to improved outcomes for patients. By sharing insights and potential data on the AI platform, physicians may promote greater communication among other doctors and patients ( 54 ). This way, physicians can make better decisions by accessing the patients’ data and opinions from colleague doctors.…”
Section: Resultsmentioning
confidence: 99%
“…ChatGPT application is widely used in training curricula in medicine. Although ChatGPT application is still in the research stage, it has shown promising results, particularly in ocular cancer, where the potential role of AI is extensively explored in the literature (53). In this context, ChatGPT serves as a valuable tool to assist researchers and practitioners in successfully transitioning to AI-based approaches in the field of ocular cancer.…”
Section: Research Implicationsmentioning
confidence: 99%
“…The rational application of ChatGPT may be an effective approach. Clinical application studies currently exist in various processes of clinical work, such as diagnosis, 24,25 decision-making instruments, 26 and generating reports, 27 and some of these studies have shown that ChatGPT is effective in improving the efficiency of nursing care, 28,29 assisting in diagnosis, 30 and so on, but it is important to note that these studies have not been practically deployed in the clinical setting and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Extending its application to diverse scenarios within OMFS, we consider another instance involving craniofacial trauma. In cases where a surgeon is confronted with multiple fractures, ChatGPT proves its versatility by processing extensive information, including medical histories, imaging results, and relevant literature 12 . This model’s proficiency in generating timely insights into optimal treatment strategies exemplifies its utility in addressing varied and complex scenarios, demonstrating its potential to enhance precision and decision-making in the field of OMFS.…”
Section: Enhanced Specificity For Oral and Maxillofacial Surgery (Omfs)mentioning
confidence: 99%